Beyond Amitriptyline: A Pediatric and Adolescent Oriented Narrative Review of the Analgesic Properties of Psychotropic Medications for the Treatment of Complex Pain and Headache Disorders - Robert Blake Windsor; Michael Sierra; Megan Zappitelli; Maria McDaniel (MDPI AG, 2020)
Children and adolescents with recurrent or chronic pain and headache are a complex and heterogenous population. Patients are best served by multi-specialty, multidisciplinary teams to assess and create tailored, individualized pain treatment and rehabilitation plans. Due to the complex nature of pain, generalizing pharmacologic treatment recommendations in children with recurrent or chronic pains is challenging. This is particularly true of complicated patients with co-existing painful and psychiatric conditions. There is an unfortunate dearth of evidence to support many pharmacologic therapies to treat children with chronic pain and headache. This narrative review hopes to supplement the available treatment options for this complex population by reviewing the pediatric and adult literature for analgesic properties of medications that also have psychiatric indication. The medications reviewed belong to medication classes typically described as antidepressants, alpha 2 delta ligands, mood stabilizers, anti-psychotics, anti-sympathetic agents, and stimulants.